KASIH SAYANG KELUARGA DALAM KARYA SENI GRAFIS (STENCIL PRINT) - Rovie Fitrinanda Wirawan; Irwan Irwan (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize the family as a reminder of the community that it is so important to maintain the harmony of a family in the form of graphic art with the Stencil Print technique. Showing various life situations in the family. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. The author successfully created 10 works with the titles: Happiness, Motivation, Closeness, Warmth, Togetherness, Harmony, Communication, Substitute role, Attention, Hope.Keywords: Family, Graphic, Stencil Print